PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi pada Pelanggan Sriwijaya Air Rute Semarang-Jakarta) - Risko Putra; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2017)
This research was motivated by the needs of the people are increasing, including in the field of transport. Air transport is one of the most demanding public transport at this time. Sriwijaya Air as one of the companies engaged in the air transport services will always give the best of everything in order to create customer satisfaction. But from 2012 to 2015 decline in the number of passengers Sriwijaya Air. This indicates the performance of Sriwijaya Air is decreased and result in the decreased levels of customer satisfaction and customer loyalty followed by a decrease in the level of Sriwijaya Air. The purpose of the researchis to determine the influence of price and service quality to customer loyalty, through customer satisfaction of Sriwijaya Air customer route Semarang-Jakarta. The sample in this research were 100 respondents with the sampling technique purposive sampling. The analysis used in this research is the path analysis using with SPSS program 20.0, which previously tested the validity and reliability, coefisien correlation, coefisien determination, simple linear regression and multiple linier regression, and tested the significance. The results showed that price and quality service partially affects customer satisfaction and customer loyalty. And simultaneously also showed that the price and quality service affects customer satisfaction and customer loyalty. Variable quality service gives greater influence on customer satisfaction and customer loyalty of the variable price.